A STEWART PLATFORM AS A FBW FLIGHT CONTROL UNIT - Omurlu, Vasfi Emre; Yildiz, Ibrahim (SLOVAK UNIV TECHNOLOGY, 2011)
A variety of flight control units have been put into realization for navigational purposes of spatially moving vehicles (SMV), which is mostly manipulated by 2 or 3 degrees-of-freedom (DOF) joysticks. Since motion in space consists of three translational motions in forward, side and vertical directions and three rotational motions about these axis; with present joystick interfaces, spatial vehicles has to employ more than one navigational control unit to be able to navigate On all required directions. In this study, a 3 x 3 Stewart-Platform-based FBW (Fly-By-Wire) flight control unit with force feedback is presented which will provide single point manipulation of any SMVs along three translational and about three rotational axis. Within the frame of this paper, design, capability and the advantages of the novel system is mentioned. Kinematics of a Stewart Platform (SP) mechanism employed and its motion potentials is presented by simulations and workspace of the system is evaluated. Dynamic analysis by Bond-Graph approach will be mentioned. Mechatronic design of the complete structure is discussed and force reflection capability of the system with simulations is pointed out using stiffness control. Finally, the possible future work of the subject is discussed which may include the feasible solutions of the SP in terms of size and safety when implementing inside a cockpit.
Keywords: flight control; stewart platform; spatial motion; force feedback control; bond-graph modeling; workspace analysis; 6-DOF PARALLEL MANIPULATORS; DYNAMIC-ANALYSIS; WORKSPACE; Engineering